LITERASI MEDIA TERHADAP PERSEPSI PEREDARAN DISINFORMASI COVID-19 MEMILIKI PENGARUH LEBIH DARI 50% DI KOTA BATAM - Sianturi, Yunita Meyer; Purwanti, Angel (LPPM Universitas Putera Batam, 2021)
Indonesia is one of the highest countries with internet users in the world. Around 175,4 million people of 272,1 million population are connected to the internet (Hootsuite Survey, 2020). The internet is used not only to access information, but also to spread the information itself. Around 94% from the survey says that smartphones are the most used device to access the internet. With the smartphones themselves spreading information is easier to do and it can be done from anywhere and anytime. The information can also be spread by social media or instant messaging application. That way there is a possibility that the information spread is not credible. To prevent the spreading of disinformation media literacy is needed. Literacy is one’s ability to read and write (Potter, 2019:51). In this case media literacy is the most basic skill needed to encounter the media exposure (Fitryarini, 2016:58). This research uses the descriptive quantitative design. This research uses the IBM SPSS 25 as data processing software. The result show that the t value for the independent variable media literacy (X) is 19,117 towards dependent variable perception (Y) with significance value 0,000. This shows that the t value 19,117 > t table 1,652 with significance 0,05, in conclusion H0 is declined and Ha is accepted.